" The role of the Internet in the promotion of tourism services "Applied Study on Tourism Offices in Jordan - Al-mawajdah, Nour Khaldoun Khalif (Arab Journal for Sciences and Research Publishing, 2017)
The tourism sector is one of the sectors that contribute to the creation of gross domestic product in Jordan and in accordance with the stated estimates, this sector accounts for about 10% of the gross domestic Product. Thus, there is a justification regarding the interest of the so- called tourist industry which became one of the most important sectors in most of the countries; so there is a continuous effort to develop this sector and reap the benefits of that in relation to the different economies. Jordan has a comparative advantage due to its strategic location, historical monuments, religious places, as well as the possibility of using the therapeutic, educational and recreational tourism and others in the near future. In the current time we have to develop a strategy for tourism choices, as well as a clear vision about the touristic quality, which aims at developing it. Therefore, we can say that there is a need to expand the overall usefulness of tourism by educating the people involved with tourism and highlighting its role and economic usefulness. Thus, this study addresses the definition of the concept of tourism promotion and its relationship with the concept of tourism marketing as a broader context, in addition to showing the importance of the internet in tourism promotion, and the requirements of their application, given the speed of the successive changes in the tourism work environment both on the national and international levels. The study focuses on identifying the extent of the information technology impact in general and the internet in particular as well as applying them in the touristic offices that are available in Wadi Mousa by highlighting the efficiency of the website on activating tourism, planning for the touristic area and identifying the impact of the network as a means of communication between the elements of touristic attraction in the touristic area and between the tourists regardless their nationalities. The results showed that the information accuracy via the internet in terms of the touristic offices increases the touristic attraction. The results also showed that emphasizing the activation of tourism promotion advertisements as well as the ideal planning for the programs and touristic services via the internet through the websites, particularly the government websites that provide valid information is the only means for solving all the problems of tourism promotion. In the light of the competitive and structural challenges facing the industry and agriculture sectors, the tourism sector is considered as the most prepared one in the short as well as the medium run in order to contribute to reaching the hoped growth rates, creating work opportunities as well as increasing the resources.
Keywords: Tourism planning; Tourism promotion; Objectives of tourism promotion; Forms of tourism promotion; Tourism